Visual aesthetics of bamboos woven motifs and patterns in Malay architecture within northern Malaysia / Mariam Idris - Idris, Mariam (2017)
The decorative motifs and patterns of Malay bamboo architecture appear in most of the buildings in northern part of Malaysia. Bamboo plant reduces the negative effect to the environment unlike water, air and land pollution. The Malay's aesthetics value in bamboo based materials has not been highlighted since it involves hard work activity in traditional way. The challenge arises in its handling, application and durability. The present research employs qualitative research encompasses the concept of descriptive design. The techniques denote a documental photography including the materials in its surrounding. The latter focused upon possible differences in types of motifs and patterns among Malay architecture in Kedah and Perak through design arrangement and weaving composition.